PENGEMBANGAN MODUL BERBASIS KEARIFAN LOKAL KABUPATEN SANGGAU KELAS IV SUBTEMA LINGKUNGAN TEMPAT TINGGALKU - Moh. Farid Nurul Anwar; Chusnul Chotimah; Yulita Sulianti Pani (Bajang Institute, 2023)
The contents of student books from the government are less contextual and not following the area where students live, so it needs to be developed. Research and development of modules based on local Wisdom in Sanggau Regency Sub-theme of My Living Environment Learning 3 Class IV SDN 10 Jemongko aimed to develop valid and effective modules. This research and development were carried out using a modified Borg and Gall procedure. The validation of materials, linguists, and design experts showed that the average percentage of module validity is 90.4%, 90.4%, and 88.9%, respectively. The average value of the proportion of teacher and student responses is 90.2%. The value of student learning outcomes in the module is 90.8. These results showed that the module based on local wisdom in Sanggau Regency Sub-theme of My Living Environment Learning 3 Class IV SDN 10 Jemongko is valid and effective